The Impact of Language of Instruction in Schools on Student Achievement : Evidence from Malaysia Using the Synthetic Control Method - Soh, Yew Chong (World Bank, Washington, DC, 2021)
This paper employs the synthetic control method to examine the impact of using a non-native language as the medium of instruction in schools on a student’s learning. Exploiting an unanticipated policy change in Malaysia and using data from the Trends in International Mathematics and Science Studies, the results show that changing the medium of instruction negatively influenced eighth graders’ achievement in mathematics and science. The differential performance, by year and gender, suggests that using a non-native language throughout a student’s schooling may have greater negative impact on the student’s learning than switching the language of instruction in the middle of the student’s schooling does. This paper sheds light on the various manners in which a language policy can adversely affect a student’s learning outcomes. It also highlights how the transition in switching the language of instruction in schools can be implemented more effectively to mitigate its adverse effects.